Sosialisasi Stop Bullying sebagai Upaya Pencegahan Perundungan di SDN Tonjong 1 Tajurhalang Kabupaten Bogor - Eda Laelasari; Naulatun Nafisah; Mohamad Darmawan; Falakhurromadhoni Jidan (El-Mujtama: Jurnal Pengabdian Masyarakat, 2026)
Bullying is a serious issue in education, including at the elementary school level. The “Stop Bullying” socialization implemented by IAIN Laa Roiba students in the Community Service Program (KKN) at SDN Tonjong 1 Tajurhalang, Bogor Regency aimed to provide students with an understanding of the definition, forms and negative impacts of bullying, while fostering awareness of mutual respect and the importance of avoiding such behavior. The activity was carried out in two sessions using interactive presentations, discussions, educational games and role-play simulations. The results indicated an increase in students’ knowledge about bullying, the development of empathy and a commitment to refrain from engaging in any form of bullying. The school appreciated the activity as it aligned with efforts to prevent bullying, which has become a major concern in Indonesian education, while the community also supported the program’s sustainability. Theoretically, this activity highlights the crucial roles of teachers, schools, parents and the community in creating a safe, child-friendly and bullying-free learning environment.